Analisis Kegagalan dan Usulan Perbaikan Produk Lemari Menggunakan Metode FMEA dan FTA di CV. Arafah Jaya Purwakarta - Roby Ramdan; Fajar Rizky Ramdhani; Osep Hizuzaman (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study aims to analyze product failures and propose improvement actions for cabinet products at CV. Arafah Jaya Purwakarta. Based on production data from November 2024 to April 2025, cabinet products showed the highest defect rate compared to other products, reaching 13%. The most common defects include wood cracks, warped wood, and brittle wood. Failure Mode and Effect Analysis (FMEA) was applied to identify and prioritize potential failures based on the Risk Priority Number (RPN), while Fault Tree Analysis (FTA) was used to systematically determine the root causes of failures. The analysis results indicate that the main causes of defects are related to substandard raw material quality, environmental conditions, and insufficient supervision during the production process. Based on the results of FMEA and FTA, improvement proposals were developed using the 5W+1H approach, focusing on improving raw material selection, controlling wood storage conditions, and enhancing work procedures and production supervision. These improvement efforts are expected to reduce defect rates and improve the overall quality of cabinet products.